Kesehatan Mental sebagai Aspek Penting dalam Intervensi Pasca Bencana - Hakim, Ganesha Rahman; Ismunandar, Helmi; Sutarto, Sutarto (Medula, 2024)
Indonesia experiences a high occurrence of natural disasters. Throughout the year 2022, a total of 3,544 disasters were recorded in Indonesia. Disasters can be defined as events that threaten lives and disrupt communities, resulting from both natural and non-natural factors. Disasters have broad impacts on physical and mental health. The population affected by disasters may exhibit traumatic reactions and show psychological symptoms. Some individuals require assistance to cope with their traumatic reactions. Psychological First Aid (PFA) is an effective psychological intervention that can provide support and a sense of safety to individuals affected by disasters. The principles of PFA involve providing emotional support and connecting the victim with the necessary assistance. PFA is conducted using three principles: look, listen, and link. The first step involves identifying victims in need of psychological assistance, followed by listening and calming the victims. Finally, the helper will assist the victim in obtaining further necessary assistance. PFA has a positive impact on the mental health of victims, reducing anxiety, depression, emotional distress, and feelings of fear. Additionally, PFA can provide victims with a sense of security and help them reconnect with available assistance.